How to do a superior performance appraisal - Swan, William S.; Margulies, Phillip (Wiley, 1991)
A systematic, step-by-step guide to doing performance appraisals, which discusses how they can be used to increase productivity, profitability and morale. The book includes checklists and information sheets to help implement the strategies presented.